The importance and effects of colors in accommodation units for homeless people - Czafík, Michal; Görner, Karol; Štefancová, Lucia (Journal of Architecture and Urbanism, 2025)
Designing accommodation for homeless people requires a specific approach based on analysis, based on knowledge of the mental and physical condition of a person, their needs, and demands. The color of the living space can play an important role in a person’s social inclusion, a faster and more continuous return of a person to a full life. The research aimed to verify how much the preferences for the use of color in the interior match among the homeless people and to draw recommendations for the color application. The theoretical analysis deals with the influence of architecture on our senses. Special attention is paid to the effects of sunlight, especially on the visible light spectrum, the originator of color vision. In the research methodology, the article defines the target group of homeless people using social service accommodation and data collection procedures. The results and discussion provide an overview of color preferences among respondents and the interpretation of findings. It has been shown that homeless people form a relatively homogeneous group for which it is possible to define general color selection requirements and to set key recommendations for the application of color schemes in social services accommodation units.